The spirit of the child - Hay, David, 1935-2014 (Jessica Kingsley Publishers, 2006)
Spirituality is increasingly acknowledged to be an essential part of child development. David Hay argues for the inclusion of spiritual awareness as a cross-curricular element in the school syllabus to promote the development of morality and social cohesion. While culturally constructed pressures and the decline in institutional religion have led to the suppression of spiritual expression, children are, the author maintains, capable of profound and meaningful beliefs from an early age. A three-year research study into young children's spirituality and its survival value informs Hay's view that.